2017
DOI: 10.1371/journal.pgen.1006952
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the genetic control of gene expression following Mycobacterium leprae antigen stimulation

Abstract: Leprosy is a human infectious disease caused by Mycobacterium leprae. A strong host genetic contribution to leprosy susceptibility is well established. However, the modulation of the transcriptional response to infection and the mechanism(s) of disease control are poorly understood. To address this gap in knowledge of leprosy pathogenicity, we conducted a genome-wide search for expression quantitative trait loci (eQTL) that are associated with transcript variation before and after stimulation with M. leprae so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(61 citation statements)
references
References 59 publications
3
57
1
Order By: Relevance
“…Twin studies estimate the heritability (proportion of the variation in susceptibility attributed to genetics) to be as high as 80% but estimates vary over a substantial range [ 12 ]. The vast majority of candidate SNPs likely affects regulatory mechanisms, leading to a growing consensus that gene regulation plays a prominent role, particularly in genes subject to evolutionary selection pressures [ 7 9 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Twin studies estimate the heritability (proportion of the variation in susceptibility attributed to genetics) to be as high as 80% but estimates vary over a substantial range [ 12 ]. The vast majority of candidate SNPs likely affects regulatory mechanisms, leading to a growing consensus that gene regulation plays a prominent role, particularly in genes subject to evolutionary selection pressures [ 7 9 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…This led to the identification of 318 genes that were impacted by cis -eQTL in either stimulated or non-stimulated samples (FDR of 0.01), while 66 of these genes displayed eQTL only in one condition (response eQTL) directly demonstrating the interaction of host genetic background and pathogen exposure. Interestingly, the same study also showed that both eQTL and response-eQTL are targeted by positive selection (Manry et al 2017 ).…”
Section: Leprosymentioning
confidence: 95%
“…Recently, the impact of genetic variation on the human response to M. leprae was demonstrated by an eQTL study of whole blood cells in the presence and absence of M. leprae antigen (Manry et al 2017 ). Of particular interest was the identification of genetic regulators of host gene expression levels that depended on the presence of M. leprae .…”
Section: Leprosymentioning
confidence: 99%
“…A differential expression analysis of mRNA was conducted to investigate the transcription alterations of target genes during M. leprae infection using the available data of Gene Expression Omnibus (GEO). Two datasets were downloaded and reanalyzed: (1) dataset GEO: GSE100853, a genome-wide search for expression quantitative trait loci before and after stimulation with sonicate of M. leprae in whole-blood from 51 unrelated individuals from Vietnam with borderline leprosy [39]; (2) dataset GEO: GSE74481, which included the mRNA profiles PLOS NEGLECTED TROPICAL DISEASES in leprosy skin lesions of 24 individuals with multibacillary leprosy including 10 BB, 10 BL, and 4 LL, 20 individuals with paucibacillary leprosy consisting of 10 TT and 10 BT, 14 individuals with type I reaction, and 9 individuals with type II reaction, and normal skin biopsies of nine healthy individuals used as controls [40].…”
Section: Mrna Expression Analysismentioning
confidence: 99%